2007
DOI: 10.1117/1.2823149
|View full text |Cite
|
Sign up to set email alerts
|

Core-shell silica nanoparticles as fluorescent labels for nanomedicine

Abstract: Progress in biomedical imaging depends on the development of probes that combine low toxicity with high sensitivity, resolution, and stability. Toward that end, a new class of highly fluorescent core-shell silica nanoparticles with narrow size distributions and enhanced photostability, known as C dots, provide an appealing alternative to quantum dots. Here, C dots are evaluated with a particular emphasis on in-vivo applications in cancer biology. It is established that C dots are nontoxic at biologically relev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
102
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 121 publications
(106 citation statements)
references
References 44 publications
2
102
0
2
Order By: Relevance
“…Its applications include real-time, intraoperative detection and imaging of nodal metastases, differential tumor burden, and lymphatic drainage patterns in melanoma. Although several investigators have synthesized radiolabeled fluorescent particle probes (25,30,40), our multimodal agent has been radiolabeled with the long-lived positron-emitter iodine-124, and, thus, we believe it can provide unique longer-term pharmacokinetic clearance and targeting information over the course of days. The complementary nature of this platform, coupled with its small size (~7-nm i.d.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its applications include real-time, intraoperative detection and imaging of nodal metastases, differential tumor burden, and lymphatic drainage patterns in melanoma. Although several investigators have synthesized radiolabeled fluorescent particle probes (25,30,40), our multimodal agent has been radiolabeled with the long-lived positron-emitter iodine-124, and, thus, we believe it can provide unique longer-term pharmacokinetic clearance and targeting information over the course of days. The complementary nature of this platform, coupled with its small size (~7-nm i.d.…”
Section: Discussionmentioning
confidence: 99%
“…To address such issues and comply with regulatory and clinical practice guidelines, rigorous quantitative imaging approaches and analysis tools, such as PET, will be essential for evaluating a variety of probes undergoing preclinical testing or transitioning into early-phase clinical trials. By attaching a radiolabel to the particle surface, the clinical potential of these molecularly targeted probes can be sensitively rescent particle platforms have been investigated (23)(24)(25)(26), only Cornell dots (C dots) meet the aforementioned criteria and have received the first FDA-approved investigational new drug approval of their class and properties for a first-in-human clinical trial. Surface functionalized with small numbers of targeting peptides (cyclic arginine-glycine-aspartic acid [cRGDY] peptides) and longlived radiolabels, this α v β 3 integrin-targeting particle tracer has a unique combination of structural, optical, and biological properties: bulk renal clearance (10), favorable targeting kinetics, lack of acute toxicity, superior photophysical features, and multimodal (PET-optical) imaging capabilities.…”
Section: Introductionmentioning
confidence: 99%
“…23,26 Inorganic quantum dots exhibit significantly enhanced fluorescent performance for bio-imaging. [234][235][236] In addition, GQDs possess unique optical properties such as pH-dependent and upconversion fluorescence behaviors, and GQDs are extensively used for cellular imaging in cells, organs, or tissues in this region. 237,238 Recently, Chen et al 239 reported the synthesis of composites of dextran-coated Fe 3 O 4 NPs and GO (Fe 3 O 4 -GO) as T2-weighted contrast agents for efficient cellular magnetic resonance imaging (MRI).…”
mentioning
confidence: 99%
“…This can be accomplished by covalently linking the dye molecule to a silica precursor, which can then be utilized in the synthesis of the silica nanoparticles through the classic Stöber synthesis method [102,104]. This same strategy can also be used to create more highly structured core-shell particles as well [104][105][106]. When using polar dye molecules, it is also possible to use the micro-emulsion method of synthesis; the particles are created in the water droplets of water in oil microemulsion and the dye is physically entrapped inside of the particles [102].…”
Section: Encapsulated Fluorophoresmentioning
confidence: 99%